Depth refuge and the impacts of SCUBA spearfishing on coral reef fishes. - Steven J Lindfield; Jennifer L McIlwain; Euan S Harvey (PLoS ONE, 2014)
In recent decades, spearfishing with SCUBA has emerged as an efficient method for targeting reef fish in deeper waters. However, deeper waters are increasingly recognised as a potential source of refuge that may help sustain fishery resources. We used a combination of historical catch data over a 20-year time period and fishery-independent surveys to investigate the effects of SCUBA spearfishing on coral reef fish populations in the southern Mariana Islands. Two jurisdictions were studied; Guam, where SCUBA spearfishing is practiced, and the nearby Commonwealth of Northern Mariana Islands (CNMI), where SCUBA spearfishing has been banned since 2003. Fishery-independent data were collected using baited remote underwater stereo-video systems (stereo-BRUVs) stratified by depth, marine protected area status and jurisdiction. Herbivores (primary consumers) dominated spearfishing catches, with parrotfish (scarines) and surgeonfish/unicornfish (acanthurids) the main groups harvested. However, the large, endangered humphead wrasse (Cheilinus undulatus) was the main species by weight landed by SCUBA spearfishers. SCUBA spearfishing was associated with declining size of scarines over time and catches shifting from a dominance of large parrotfishes to a mixed assemblage with increasing proportions of acanthurids. Comparisons between Guam and the nearby CNMI revealed differences in the assemblage of fished species and also greater size of scarines and acanthurids in deep water where SCUBA fishing is banned. These results suggest that SCUBA spearfishing impacts reef fish populations and that the restriction of this fishing method will ensure refuge for fish populations in deeper waters. We recommend a ban on SCUBA spearfishing to preserve or aid the recovery of large, functionally important coral reef species and to improve the sustainability of coral reef fisheries.